Perancangan Sistem Pendataan Permohonan Surat Izin Mendirikan Bangunan di Kecamatan Lubuk Sikarah Kota Solok - Noviardi, Refli; Fryonanda, Harfebi (KALBISCIENTIA Jurnal Sains dan Teknologi, 2020)
This research has been done on Lubuk Sikarah subdistrict office city of Solok by collectingdata because the system that used to work still not optimal. Therefore, analysis of the data collected bythe system design tool that aims to optimized IMB data processing using Java Netbean programminglanguage and database MYSQL. This research method used is a field of research, there are researchlibraries and research laboratories. Thus, it produced a new system analysis using tools such as ASI(FlowInformation System), DFD(Data Flow Diagram), ERD(Entity Relationship Diagram), and the ContextDiagram. These tools will be generated several interrelated files in a database management. And thenew system is expected to improve the quality of IMB petition data processing sistem on suddistrict ofLubuk Sikarah Office.